Judging school discipline the crisis of moral authority - Arum, Richard (Harvard University Press, 2003)
Reprimand a class comic, restrain a bully, dismiss a student for brazen attire - and you may be facing a lawsuit, costly regardless of the result. This reality for today's teachers and administrators has made the issue of school discipline more difficult than ever before - and public education thus more precarious. This is the troubling message delivered in Judging School Discipline, an account of how decades of mostly well-intended litigation have eroded the moral authority of teachers and principals and degraded the quality of American education." "Judging School Discipline casts a backward glance at the roots of this dilemma to show how a laudable concern for civil liberties forty years ago has resulted in oppressive abnegation of adult responsibility now. In a rigorous analysis enriched by descriptions of individual cases, the book explores 1,200 cases in which a school's right to control students was contested."--Jacket.